Processing of the intracellular form of the west Nile virus capsid protein by the viral NS2B-NS3 protease: an in vitro study. - Yamshchikov, V F (1994)
According to the existing model of flavivirus polyprotein processing, one of the cleavages in the amino-terminal part of the flavivirus polyprotein by host cell signalases results in formation of prM (precursor to one of the structural proteins, M) and the membrane-bound intracellular form of the viral capsid protein (Cint) retaining the prM signal sequence at its carboxy terminus. This hydrophobic anchor is subsequently removed by the viral protease, resulting in formation of the mature viral capsid protein found in virions (Cvir). We have prepared in vitro expression cassettes coding for both forms of the capsid protein, for the prM protein, for the C-prM precursor, and for the viral protease components of West Nile flavivirus and characterized their translation products. Using Cint and Cvir translation products as molecular markers, we have observed processing of the intracellular form of the West Nile capsid protein by the viral protease in vitro both upon cotranslation of the C-prM precursor and the viral protease-encoding cassette and by incubation of C-prM translation products with a detergent-solubilized extract of cells infected with a recombinant vaccinia virus expressing the active viral protease. The cleavage of Cint by the viral protease at the predicted dibasic site was verified by introduction of point mutations into the cleavage site and an adjacent region. These studies provide the first direct demonstration of processing of the intracellular form of the flavivirus capsid protein by the viral protease.